Turbulence modulation and heat transfer enhancement in channels roughened by cube-covered surface. (30th March 2018) - Li, Qing-Xiang; Pan, Ming; Dong, Yu-Hong
Highlights: Turbulent channel flows with a cube-covered wall are investigated by DNS based on LBM. The feedbacks arising from the cube elements to momentum and energy transport are evaluated. Dependences of cube height on the drag coefficient and Nusselt number are shown. A strategy to achieve heat transfer enhancement in wall-bounded flows is examined. Abstract: Direct numerical simulations are carried out to study turbulence modification and heat transport augmentation in rough channels with minor cubes on one wall. To account for the effect of the cubes on momentum and heat transfer in wall-bounded turbulent flows, the lattice Boltzmann method which is based on a double-distribution-function and D3Q19 model is applied to perform the numerical computation. The present study focuses on the modulations of the temperature field and heat transfer process by rough wall with different cube heights. Some typical dynamic and thermal statistics, such as the mean velocities, mean temperature, velocity fluctuations, the Reynolds stresses, and turbulent heat flux are analyzed. The similar trend of temperature and velocity roughness functions illustrates there is strong correlation between the heat transfer augmentation and a drag increase in rough channel flows. A significant heat transfer enhancement (26%, by taking into account the drag consumption) is obtained with the medium-height cubes.